2018
DOI: 10.1126/sciadv.aar5770
|View full text |Cite
|
Sign up to set email alerts
|

A persulfidation-based mechanism controls aquaporin-8 conductance

Abstract: A two-step posttranslational modification of AQP8 provides a mechanism regulating plasma membrane H2O2 conductance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…The contrasts between compartments revealed in the different mutant backgrounds allowed us to address the question of how NADPH oxidase (RBOH)‐derived apoplastic H 2 O 2 would impact on intracellular H 2 O 2 dynamics. Passage of extracellular H 2 O 2 across the plasma membrane via aquaporins has been shown by several studies (Bienert & Chaumont, ; Rodrigues et al ., ; Bestetti et al ., ), but detailed assessment of subcellular impacts in vivo is lacking. To explore the intracellular impact of RBOH activation, we used multiwell fluorimetry and three different elicitor treatments; the N‐terminal flagellin fragment flg22, a partially acetylated chitosan (degree of acetylation (DA) 50%), and a fully deacetylated chitosan (DA 0%) (Melcher & Moerschbacher, ; Gubaeva et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The contrasts between compartments revealed in the different mutant backgrounds allowed us to address the question of how NADPH oxidase (RBOH)‐derived apoplastic H 2 O 2 would impact on intracellular H 2 O 2 dynamics. Passage of extracellular H 2 O 2 across the plasma membrane via aquaporins has been shown by several studies (Bienert & Chaumont, ; Rodrigues et al ., ; Bestetti et al ., ), but detailed assessment of subcellular impacts in vivo is lacking. To explore the intracellular impact of RBOH activation, we used multiwell fluorimetry and three different elicitor treatments; the N‐terminal flagellin fragment flg22, a partially acetylated chitosan (degree of acetylation (DA) 50%), and a fully deacetylated chitosan (DA 0%) (Melcher & Moerschbacher, ; Gubaeva et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gating involved the combined and coordinated action of H 2 O 2 and the gasotransmitter H 2 S in a two-step process: First, a reactive cysteine inside the extracellular vestibule of the pore (C53) is primed by sulfenylation through the passage of the transported H 2 O 2 molecules. Then, the moiety is modified by persulfidation induced by the activation of the H 2 S-producing redox-sensitive enzyme cystathionine-β-synthase (CBS), which is situated in the vicinity of the cytosolic mouth of the channel [ 164 ]. The latter modification elongates the side chain of C53 in a way that a histidine (H72), situated in the narrowest part of the pore, is displaced from its original position, leading to channel blockade.…”
Section: The Plasma Membrane As a Platform For Redox Signal Transmmentioning
confidence: 99%
“…The latter modification elongates the side chain of C53 in a way that a histidine (H72), situated in the narrowest part of the pore, is displaced from its original position, leading to channel blockade. The system has been hypothesized to function as a sensor of the levels of H 2 O 2 molecules crossing the plasma membrane [ 164 ]. Interestingly, C53 of AQP8 is highly conserved in all known peroxiporins [ 26 , 164 ], suggesting that a similar mechanism of gating could be operating in all of them.…”
Section: The Plasma Membrane As a Platform For Redox Signal Transmmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, the transcription of AQP genes ( OsPIP1;1, OsPIP1;2, OsPIP1;3 and OsPIP2;8 ) were found to be regulated by NO during seed germination (Liu et al ). Bestetti et al () showed that H 2 S regulates the AQP8‐mediated H 2 O 2 membrane transport in human cell lines. Recent technological advancement has brought many tools and techniques to evaluate solute specificity, transport kinetics and regulatory factors for AQP transport system (Deshmukh et al ).…”
Section: The Role Of Aqps As Transporters Of No and H2smentioning
confidence: 99%